2017
DOI: 10.1039/c7ra06785b
|View full text |Cite
|
Sign up to set email alerts
|

Performance of ZnMn2O4/SiO2 sorbent for high temperature H2S removal from hot coal gas

Abstract: A spinel ZnMn 2 O 4 sorbent supported on SiO 2 was fabricated using a wetness impregnation method for high temperature desulfurization. The operating parameters including operating temperature, ZnMn 2 O 4 content, space velocity, gas composition, and multiple desulfurization/regeneration cycles were evaluated to understand the optimal condition. The ZnMn 2 O 4 /SiO 2 sorbent exhibits better desulfurization performance when operating temperature is controlled above 600 C and the suitable space velocity is betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It is reported that the Fe, Mn, Cu, Zn, and Co have the favorable thermodynamic property for high-temperature desulfurization [3][4][5][6]. In the past, we have investigated a great number of soil samples for hightemperature desulfurization, and some important information was proposed [10,11].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that the Fe, Mn, Cu, Zn, and Co have the favorable thermodynamic property for high-temperature desulfurization [3][4][5][6]. In the past, we have investigated a great number of soil samples for hightemperature desulfurization, and some important information was proposed [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…With a regression fitting analysis, the proportion of Al 6 is 82.4%, 75.8%, and 78.3% for fresh and both regenerated soil samples. e proportion of Al 4 significantly increased and that of Al 6 decreased after the regeneration reaction. e reasonable explanation of this finding is likely ascribed to the fact that coordination of aluminum underwent significant Journal of Chemistrychanges resulting from the dehydroxylation or the formation of aluminosilicate under strong exothermic reaction from the regeneration process [15,16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Spinel phase oxides with the formula AB 2 O 4 (A and B are metals) are known for their high stability and diverse framework architectures. In particular, Zn-based spinel adsorbents (ZnB 2 O 4 ) with periodical [B 4 O 4 ] 4− cubical secondary building units have been reported to considerably subdue vaporization of zinc atoms during hot gas desulfurization when temperatures of the reactors were <600 • C and demonstrates the synergistic effects of ZnO as B 2 O 3 units on reaction with H 2 S in desulfurization steps [144][145][146]. Additionally, zeolites are high porosity green materials that can prevent sintering of active guest species and have been used in multiple applications, including ion exchange, catalysis, and gas adsorption [147][148][149][150][151].…”
Section: Spinel Embedded Silicoaluminophosphate Catalystsmentioning
confidence: 99%
“…The porous supports mainly contain g-Al 2 O 3 , mesoporous silica, zeolite, and carbon materials. [21][22][23][24][25][26][27] Carbon materials including activated carbon and semicoke have attracted more and more researchers' attention due to their abundant pore structure and low cost. In comparison with activated carbon, semicoke is cheaper and more easily attained.…”
Section: Introductionmentioning
confidence: 99%